Fiber-optic sensor-based remote acoustic emission measurement of composites. (26th September 2016) - Yu, Fengming; Okabe, Yoji; Wu, Qi; Shigeta, Naoki
Abstract: Acoustic emission (AE) detection functioning at high temperatures could clarify the damage process in high heat-resistant composites. To achieve the high-temperature AE detection, a remote AE measurement based on a phase-shifted fiber Bragg grating (PS-FBG) sensor with a high sensitivity over a broad bandwidth was proposed. The common optical fibers were made from glass with good heat resistance. Hence, in this method, optical fiber was used as the waveguide to propagate the AE in the composite from a high-temperature environment to the room-temperature environment wherein the PS-FBG was located. Owing to the special AE detection configuration, this method was a new adhesive method for remote measurement (ADRM). The experiment and numerical simulation revealed that the PS-FBG sensor in the ADRM configuration demonstrated accurate remote sensing for the AE signals. This was because of the good waveguide system provided by the thin optical fiber and the sensitivity of the PS-FBG sensor to the axial strain in the core of the fiber. Consequently, the remote measurement utilizing the PS-FBG sensor in the ADRM configuration has a high potential for AE detection in high-temperature conditions.